Altered N170 and compensatory mechanisms in face processing in schizophrenia: an event-related potential study - Sun, Jiajun; Liu, Qing; Sun, Hongjun; Liu, Li; Bai, Chunhui; Wang, Changming; Li, Ling (Frontiers in Psychiatry, 2026)
IntroductionImpaired face processing is a core contributor to social cognitive deficits in schizophrenia. Studies examining the N170, an event-related potential component indexing the structural encoding of faces, have yielded a puzzling inconsistency—showing reduction, no difference, or even enhancement in patients. This paradox challenges simplistic deficit models and may point to uncharacterified compensatory neural mechanisms, potentially arising from dysfunctional neural oscillations that undermine processing efficiency.MethodsFifty clinically stable patients with schizophrenia and twenty-five healthy controls performed a challenging perceptual matching task with partially occluded and unoccluded images of faces and buildings during high-density EEG recording. Our analysis specifically targeted the N170 component and its underlying neural synchrony, quantified by the phase-locking factor (PLF) in the alpha band (8–12 Hz). We directly contrasted its response to faces against a control category (buildings) to isolate face-specific processing, and contextualized these findings within the established early visual processing deficit indexed by the P1 component.ResultsWe found a significant enhancement of the N170 amplitude specifically to faces in patients versus controls (P = 0.018), with no group difference for buildings (P = 0.846). Critically, this face-specific hyper-responsiveness was accompanied by a significant reduction in alpha-band PLF for the N170 (P = 0.002), indicating impaired precision in neural synchrony despite the larger response. For a comprehensive framework, we also replicated the well-established deficit in early visual processing, as evidenced by a reduced P1 amplitude (P < 0.001).ConclusionThe combination of an enhanced N170 with impaired alpha-phase locking reveals a hyper-responsive yet inefficient and dyssynchronous face-processing network in schizophrenia. This distinctive electrophysiological profile supports a model of inefficient neural compensation, whereby the brain mobilizes greater resources in an attempt to process socially salient stimuli, but does so with poor temporal coordination, ultimately contributing to the social cognitive impairments characteristic of the disorder.